2020
DOI: 10.1186/s12891-020-3181-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct severity of phenotype in Hajdu-Cheney syndrome: a case report and literature review

Abstract: Background: Hajdu-Cheney syndrome (HCS) is a rare inherited skeletal disorder caused by pathogenic mutations in exon 34 of NOTCH2. Its highly variable phenotypes make early diagnosis challenging. In this paper, we report a case of early-onset HCS with severe phenotypic manifestations but delayed diagnosis. Case presentation: The patient was born to non-consanguineous, healthy parents of Chinese origin. She presented facial anomalies, micrognathia and skull malformations at birth, and was found hearing impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The phenotypic variability [8,27,28], a consequence of the variability of expression of NOTCH2, is evident when comparing this case to other cases diagnosed with HCS that have been published in the scientific literature. Cases such as those presented by Swan et al [29], Ades et al [12] and Takatani et al [30] all show differences in their physical appearance and clinical presentation despite having the same diagnosis.…”
Section: Discussionmentioning
confidence: 77%
“…The phenotypic variability [8,27,28], a consequence of the variability of expression of NOTCH2, is evident when comparing this case to other cases diagnosed with HCS that have been published in the scientific literature. Cases such as those presented by Swan et al [29], Ades et al [12] and Takatani et al [30] all show differences in their physical appearance and clinical presentation despite having the same diagnosis.…”
Section: Discussionmentioning
confidence: 77%
“…Some reports consider this entity as either a normal variant or an acquired condition secondary to head trauma and skull manipulations as practiced in some cultures. 1,2 Other studies have found an association of this phenomenon with skeletal dysplasia, 6,9 osteogenesis imperfecta, 2,4,12 and craniosynostosis 2,21,22 and also with rare conditions such as Menkes Disease, 23 Robinow Syndrome, 7 Primrose Syndrome 9 and ARID2 mutations. 10,24 The current study provides an informative description of this condition in a cohort of 72 fetuses.…”
Section: Discussionmentioning
confidence: 95%
“…With similar molecular and clinical findings in Serpentine fibula‐polycystic kidney syndrome and Hajdu‐Cheney syndrome, it is now accepted that the two syndromes are variable manifestations of the same mutated gene and so are the same disorder. Cardiovascular findings by Kaler et al (1990) were mostly valvular abnormalities (mitral and aortic) whereas the cardiovascular manifestations in all subsequent reports of Hajdu‐Cheney syndrome have been cardiac defects (Table 1) (Albano et al, 2007; Gray et al, 2012; Rosser et al, 1996; Sargin et al, 2013; Zeng et al, 2020). In the seven cases of Hajdu‐Cheney documented with cardiovascular manifestations, four had PDA with two associated with ventricular septal defect (VSD) and one with atrial septal defect (ASD).…”
Section: Discussionmentioning
confidence: 99%